Sosialisasi Pemanfaatan Cacahan Batang Ubikayu Segar Sebagai Alternatif Sumber Hara Kalium di Sekincau Lampung Barat - Setiawan, Kukuh; Hadi, Muhammad Syamsoel; Agustiansyah, Agustiansyah; Pramono, Eko; Kamal, Muhammad; Ardian, Ardian; Setiawan, Wawan A; Sanjaya, Purba (Jurnal Pengabdian Fakultas Pertanian Universitas Lampung, 2024)
Lampung is one of the biggest areas for cassava and also Indonesia gets the number five in the world for cassava production.  At harvest time, it would produce huge source of potassium (K) from the stem.  Unfortunately this source of K is not used yet until now.  Consequently, the objective of activity was to educate the farmers in order to use the fresh cassava stem by chipping in small size as potassium source.  This activity was conducted in Pekon Giham Sukamaju, Kecamatan Sekincau, Kabupaten Lampung Barat on January 31st 2024.  The method that was used in this activity was to discuss and present the way of producing small chip of fresh cassava stem.  The evaluation of farmer perception to understand the method was questionnaire containing 10 questions to be answered by farmers.  The result was before discussion, farmers still do not know or recognize yet that fresh cassava stem could be used as a K source.  However, after presenting the material of discussion, in general, they were interested in using small chip cassava stem for K source to fertilize the horticulture crops in their land.